Identifikasi Penggunaan Kata-kata Umpatan Representasi Hewan Dikalangan Generasi Z Kota Bandung - Iqbal, Ryanto Maulana; Pamungkas, Indra N. A; Rozaq, Miftahul (eProceedings of Management, 2024)
This research is motivated by the use of swear words as a communication culture among Generation Z. Thisphenomenon is often accepted within their environment. The swear words are predominantly represented by animalrelated terms. The purpose of this study is to examine the phenomenon of using animal representative swear words,specifically the word "dog," among Generation Z in Bandung City. This study employs an interpretive paradigm anda descriptive qualitative approach to collect and analyze data. The research was conducted offline throughobservations in the Telkom University campus environment, Bandung, and online through interviews with informantsresiding in Greater Bandung using Zoom Meetings. The results show that the use of the animal-representative term"dog" is not necessarily considered a form of swearing and that the phoneme alteration by Generation Z in usinganimal-representative swear words can be seen as positive. It can be concluded that the use of the swear word "dog"among Generation Z in Bandung City has generated insights from both cultural and linguistic perspectives. Therefore,Generation Z needs to be more aware of their language use by considering the local culture to avoidmisinterpretations. Keywords-identification, swear word, z generation.